The politics of welfare policy reforms: a comparative study of how and why changes of government affect policy making on social cash transfer programmes in Zambia and Malawi - Siachiwena, Hangala (Department of Sociology, 2021)
This thesis examines how and why social protection policy reforms happened after changes of government in Zambia and Malawi. It provides four case studies that account for the process of reforms to promote or constrain social cash transfer programmes (SCTs) by government administrations within and across the two countries over time. Recent research on social protection in Africa shows that politics matters for the expansion of programmes, but the literature discussing the specific forms of politics that drive or limit support for reforms is still emerging. There is also a paucity of evidence accounting for variation in reforms within and between countries on the continent over time. This thesis contributes to these knowledge gaps. The study argues that while donors introduced pilot SCTs in Zambia and Malawi and continue to promote reforms, domestic politics is important for understanding when, how and why national governments expanded donor supported pilots into national programmes. Therefore, the purpose of this study was to understand variation in political support for reforms within countries and to bring attention to the relative importance of partisanship. The study uses a process tracing method to understand the reform process from the mid-2000s until 2017. It draws on qualitative interviews with policy makers such as political elites, government technocrats and donor officials, and a review of policy documents. It also includes a statistical analysis of reforms in 10 East and Southern African countries to understand how Zambia and Malawi fit into a broader set of cases. The thesis demonstrates that in Zambia and Malawi, there was a greater incentive for political parties and the leaders within them to promote programmatic social protection when it had not already been seized as a mechanism for poverty reduction by the preceding government. Moreover, in cases where state support for social protection was limited, changes of government provided opportunities for international donors and government technocrats to persuade political elites in new ruling coalitions to push for faster reforms. This thesis accounts for the causal mechanisms that link changes of government and reforms and shows that the influence of international donors on political elites and the ideological, electoral and factional interests of elites and parties are crucial for understanding support for either clientelist or programmatic redistribution. Where the interests of donors and elites converge, there is a greater incentive for reforms to promote the provision of social protection. While the quantitative analysis does not provide evidence of a statistical relationship between changes of government and social policy reforms across the region, it demonstrates that democratization was associated with more social protection and shows that the interests of political elites and donor influence (controlling for other independent variables) were significant predictors of reform in the region. Furthermore, the trajectories of reform in Zambia and Malawi were similar to other low and lower middle-income democracies in the region but distinct from both upper middle-income democracies and weakly democratic low and lower middle-income countries.